Feeling Place in the City: strange ontologies, Foursquare and location-based social media - Leighton Evans (Code and the City, 2016)
Certain instances of the use of location-based social media in cities can result in deep understandings of novel locations. The contributions of other users and the information pushed to users when in particular locales can help users rapidly attune themselves to places and achieve an understanding of the place. The use of a computational device and location-based social networking to achieve this understanding indicates an alteration in the achievement of placehood using computational technology. Practices and methods of understanding place can, in some situations, be delegated to the device and application. This paper explores how the moment that place is appreciated as place (that is, as a meaningful existential locale) can be reconciled with the delegation of the epistemologies of placehood to a computational device and location-based social media application. Drawing on data from an ethnographic study of Foursquare users, the phenomenological appreciation of place is understood as co-constituent between the device, application and the mood of the user. Code and computational devices are contextualised as a constant foregrounding presence in the city, and the engagement of the user, device, code and data in understanding place is a moment of revealing that is co-constituent of all these elements. This exploratory paper engages Peter Sloterdijk’s theory of spheres as a framework to understand how these four elements interact, and how that interaction of elements can orient a user to a revealing of the city that can be understood as a phenomenological revealing of place.